Mycotic aneurysm due to Magnusiomyces capitatus complicating a second liver transplant in a colonized patient - Charles Gibert; Marie Wan; Matthieu Arsicot; Ugo Huvelle; Thomas Penhoat; Yatrika Koumar; Charline Miossec; Florence Persat; Florent Valour; Jean Menotti; Pauline Tirard-Collet (International Journal of Infectious Diseases)
This report presents an extremely rare case of a fungal mycotic aneurysm due to Magnusiomyces capitatus in a 51-year-old woman who is immunocompromised. The diagnosis was based on multiple computed tomography scans and the identification of the pathogen via sequencing of the internal transcribed spacer region. Long-term treatment with caspofungin for previous candidemia likely promoted the dissemination of this intrinsically echinocandin-resistant fungus from colonization sites in the lungs and rectal area. Long-term suppressive antifungal therapy with voriconazole and subsequently with posaconazole, combined with multiple surgical procedures, led to an improvement in the patient's condition. This case highlights the importance of considering a patient's comprehensive microbiological history and reassessing antimicrobial therapy in cases of nonimprovement or relapse.